2001
DOI: 10.1074/jbc.m011769200
|View full text |Cite
|
Sign up to set email alerts
|

Dimethyl Sulfoxide Affects the Selection of Splice Sites

Abstract: Depending on the cell lines and cell types, dimethyl sulfoxide (Me 2 SO) can induce or block cell differentiation and apoptosis. Although Me 2 SO treatment alters many levels of gene expression, the molecular processes that are directly affected by Me 2 SO have not been clearly identified. Here, we report that Me 2 SO affects splice site selection on model pre-mRNAs incubated in a nuclear extract prepared from HeLa cells. A shift toward the proximal pair of splice sites was observed on pre-mRNAs carrying compe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 44 publications
(49 reference statements)
1
11
0
Order By: Relevance
“…It has been reported that Me 2 SO affects the selection of splice sites and causes a shift toward the proximal pair of splice sites on pre-mRNAs carrying competing 5Ј-splice sites or competing 3Ј-splice sites (19). We did not observe any morphological changes when budding S. cerevisiae cells were treated with 10% Me 2 SO (Fig.…”
Section: Me 2 So Concentration and Duration Of Exposure-s Cerevisiaementioning
confidence: 63%
See 1 more Smart Citation
“…It has been reported that Me 2 SO affects the selection of splice sites and causes a shift toward the proximal pair of splice sites on pre-mRNAs carrying competing 5Ј-splice sites or competing 3Ј-splice sites (19). We did not observe any morphological changes when budding S. cerevisiae cells were treated with 10% Me 2 SO (Fig.…”
Section: Me 2 So Concentration and Duration Of Exposure-s Cerevisiaementioning
confidence: 63%
“…Thus, the effect of Me 2 SO varies depending on the cell line and cell type. At the molecular level Me 2 SO is known to affect RNA splicing and causes a shift toward the proximal pair of splice sites on pre-mRNAs carrying competing 5Ј-splice sites or competing 3Ј-splice sites (19).…”
mentioning
confidence: 99%
“…A recent work has shown that DMSO can alter premRNA splicing by interfering with the recruitment of splicing factors (Bolduc et al, 2001). This observation led us to ask whether exon 16 inclusion in mature 4.1R Spi-1/PU.1 regulates erythroid pre-mRNA splicing O Théoleyre et al mRNA in DMSO-treated MEL cells could reflect such a direct effect of DMSO.…”
Section: Resultsmentioning
confidence: 99%
“…Whether these effects result from a direct interference of DMSO with one step or the other of mRNA metabolism is an issue that has just begun to be addressed. Hence, it has recently been shown that DMSO activates splice site selection and enhances SR protein activity in HeLa extracts (Bolduc et al, 2001 Erythroid-specific splicing of 4.1R pre-mRNA is affected by Spi-1/PU.1, but not by Fli-1…”
Section: Splicing Of Exon 16 In Differentiating Mel Cells Is Regulatementioning
confidence: 99%
See 1 more Smart Citation